Gender Disparities in Dropping out of High School Students and their Level of Depression - Salim, Airin; Sultana, Rehana; Akhter, Syeda Sharmina; Azim, Sabrina Fahmida; Hoshen, Md Minuddin; Islam, Md Zakirul (Eastern Medical College Journal, 2022)
Background: A drop-out can be defined as a child who enrols in school but fails to complete the relevant level of the educational cycle. It is usually associated with non-enrolment and a lower percentage of girls than boys in the school system. High school dropouts are more likely to be on welfare, have poorer health, have reduced intergenerational mobility, become teenage parents, unemployed, depressed, have substance abuse problems, engage in violent behaviours, and end up incarcerated. Adolescent depression is a mental and emotional disorder affecting adolescents and teens. According to WHO, globally depression is the number one cause of illness and disability in adolescent age group. Depression increases a teen’s risk for attempting suicide by 12 times and 30% of teens with depression also develop a substance abuse problem. Objective: To find out the gender disparities in dropping out of high school students and their level of depression. Methodology: This cross-sectional study was done in Adarsha Sadar, Cumilla, Bangladesh in between January 2014 to December 2014. Study sample was 339 adolescents of 13-19 years of that area. By purposive sampling technique data were collected through a pretested, semi-structed, interview questionnaire. Back Depression Inventory scale was used to assess the level of depression. Results: Proportion of male drop out adolescent was 54% and female drop out adolescents 46%. 44.5% adolescents had depression and a positive association was found between adolescent depression and dropping out from high school. Conclusions: There is an apparent gender gap among the high school dropouts, with more male adolescents dropping out than females. A positive association was found between the high school dropouts and the development of adolescent depression. Eastern Med Coll J. Jan 2023; 8 (1), 1-5